Evaluation of The Effects of Intravenous Magnesium Sulphate on Haemodynamic Parameters In Patients Undergoing Laproscopic Cholecystectomy - Rasheed, Eshana; Modak, Anjali; Singam, Amol (International Journal of Psychosocial Rehabilitation, 2020)
Magnesium has a property of inhibiting catecholamine release and it can cause vasoconstriction by stimulating vasopressin. we analysed whether magnesium sulphate iv can attenuate the haemodynamic stress response while creating pnemoperitonem during laproscopy cholecystectomy. 60 patients undergoing laproscropic cholecystectomy were divided into two groups,and magnesium group received magnesium sulphate 50mg/kg before achieving peritoneum and control group was given normal saline.heart rate,BP,MAPand end tidal carbon dioxide were measured. SBP,DBP and MAP, are expected to be high in the control group. Intravenous magnesuium sulphate provide haemodynamic stability in patients undergoing laproscopic surgeries.this may be because of reduction in vasopressin and catecholamine release.